Validation of the Padova Prognostic Score for Colitis in Predicting Long-Term Outcome After Restorative Proctocolectomy - Angriman, Imerio; Colangelo, Annaclaudia; Mescoli, Claudia; Fassan, Matteo; D’Incà, Renata; Savarino, Edoardo; Pucciarelli, Salvatore; Bardini, Romeo; Ruffolo, Cesare; Scarpa, Marco (Frontiers in Surgery, 2022)
Background In 10-20% of cases it is impossible to make a differential diagnosis between ulcerative colitis and Crohn's colitis. A 50% failure rate of J pouch ilea-anal anastomosis is observed in Crohn's colitis. In 2009, we created the Padua Prognostic Score for Colitis (PPSC) to predict the long-term clinical and functional outcome and quality of life of patients undergoing restorative proctocolectomy with J pouch. The aim of the present study is to establish and validate the accuracy of a prognostic score for chronic inflammatory bowel diseases (IBD). Patient population and methods The PPSC was created in 2009 by integrating clinical and histological information of patients undergoing RPC. It included preoperative perianal abscess or fistula, rectal sparing, terminal ileum involvement, skip lesions and histological diagnosis of indeterminate colitis or Crohn’s colitis on the operative specimen. The validity of this score was tested in predicting postoperative abscess or fistula, anal canal disease, pouchitis, pouch failure and new diagnosis of Crohn's disease. Correlation analysis, ROC curve analysis and survival analysis were used to validate the PPSC in a different cohort from the previous one. Results We retrospectively enrolled in this study 138 consecutive patients undergoing CPR for ulcerative colitis (n=127) or indeterminate colitis (n=11) in our institution since 2005 to 2020. In this period, we observed 11 patients with postoperative abscess or fistula, 3 with anal canal disease, 40 with pouchitis, 6 with pouch failure and 6 with new diagnosis of Crohn's disease. In the new validation cohort, the PPSC confirmed to have a good accuracy in predicting the onset of postoperative CD (AUC=74.5%, p=0.018). Kaplan Meier curves demonstrate how a PPSC over 1 can reliably predicts the long-term onset of, pouchitis (p=0.002) and anal abscess or fistulae (p=0.04). Conclusions In this validation study we confirmed the accuracy of the PPSC in predicting postoperative fistulas or abscesses and pouchitis. Therefore, we believe that in clinical practice patients with a PPSC score greater than 1 should be warned of this risk of possible Crohn ‘s disease diagnosis and pouch failure.